Tradisi “Toron” sebagai Media Penanaman Semangat Silaturrahmi dan Toleransi Masyarakat Madura - Mahbubah, Latifatul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
Toron is an annual socio-cultural phenomenon in which Madurese migrants from various regions return to their hometowns, especially before Islamic holidays. This study aims to analyze and describe the role and meaning of the Madurese tradition of homecoming in the context of strengthening ties and fostering tolerance amidst the social diversity of the Madurese community. This study is a qualitative study in which data collection uses interviews, documentation, and observation. The results show that the tradition and culture of